Representing n-ary relations in the Semantic Web. (18th November 2019) - Giunti, Marco; Sergioli, Giuseppe; Vivanet, Giuliano; Pinna, Simone
Abstract: Knowledge representation is a central issue for Artificial Intelligence and the Semantic Web. In particular, the problem of representing n- ary relations in RDF-based languages such as RDFS or OWL by no means is an obvious one. With respect to previous attempts, we show why the solutions proposed by the well known W3C Working Group Note on n- ary relations are not satisfactory on several scores. We then present our abstract model for representing n- ary relations as directed labeled graphs, and we show how this model gives rise to a new ontological pattern ( parametric pattern ) for the representation of such relations in the Semantic Web. To this end, we define PROL (Parametric Relational Ontology Language). PROL is an ontological language designed to express any n- ary fact as a parametric pattern, which turns out to be a special RDF graph. The vocabulary of PROL is defined by a simple RDFS ontology. We argue that the parametric pattern may be particularly beneficial in the context of the Semantic Web, in virtue of its high expressive power, technical simplicity, and faithful meaning rendition. Examples are also provided.